Co-Ni/HZSM-5 Catalyst for Hydrocracking of Sunan Candlenut Oil (Reutealis trisperma (Blanco) Airy Shaw) for Production of Biofuel - Muhammad Al Muttaqii; Lenny Marlinda; Achmad Roesyadi; Danawati Hari Prajitno (The Journal of Pure and Applied Chemistry Research, 2017)
The production of biofuel by hydrocracking of Sunan candlenut oil as renewable energy can substitute fossil energy. The purpose of this work is to produce biofuel by hydrocracking of Sunan candlenut oil with Co-Ni/HZSM-5 catalyst. The catalyst was prepared by incipient wetness impregnation method. The characterization of catalyst was determined by X-Ray Diffraction (XRD) and nitrogen adsorption-desorption isotherms. The functional groups of the hydrocarbon was determined by Fourier Transform Infrared (FT-IR). The hydrocarbon composition was determined by Gas Chromatography Mass Spectrometry (GC-MS). The results showed that biofuel composition consist of 0.14 area% isoparaffins, 12.29 area% cycloparaffins, 6.87 area% normal paraffins, 4.18 area% olefin, and 10.52 area% aromatics, and oxygenated compounds including 35.03 area% carboxylic acids. It was necessary to be done that the oxygenated compounds in biofuel were eliminated to produce the abundant paraffin hydrocarbons at reaction temperature above 350 oC.